Love-Based Curriculum as a Humanistic Approach to Islamic Religious Education in the Era of Independent Learning - Saiful Bahri (EDUJAVARE: International Journal of Educational Research, 2026)
The background of this study is rooted in the need to transform Islamic Religious Education from a predominantly doctrinal and cognitive model into a more humane, student-centered, and value-oriented learning process that responds to the moral, emotional, and social challenges of contemporary education. This study examines the Love-Based Curriculum as a humanistic approach to Islamic Religious Education in the era of Independent Learning. Using a qualitative library research design, this study analyzes books, journal articles, and relevant academic publications published from 2020 onward, focusing on the intersection of humanistic education, Islamic Religious Education, curriculum development, and the implementation of Kurikulum Merdeka in Indonesia. The findings show that the Love-Based Curriculum provides a relevant conceptual framework for strengthening Islamic Religious Education by integrating the values of love, compassion, empathy, mercy, and human dignity into curriculum objectives, learning processes, and educational relationships. This approach aligns closely with the principles of Independent Learning, particularly in promoting student-centered learning, contextual instruction, reflective practice, and holistic character formation. The study also finds that the Love-Based Curriculum has important pedagogical implications, including the transformation of teacher roles from knowledge transmitters to compassionate facilitators, the use of dialogical and experiential learning methods, and the development of authentic assessments that capture both cognitive achievement and value internalization.